2009
DOI: 10.1074/jbc.m109.038133
|View full text |Cite
|
Sign up to set email alerts
|

Amino Acid Position-specific Contributions to Amyloid β-Protein Oligomerization

Abstract: Understanding the structural and assembly dynamics of the amyloid ␤-protein (A␤) has direct relevance to the development of therapeutic agents for Alzheimer disease. To elucidate these dynamics, we combined scanning amino acid substitution with a method for quantitative determination of the A␤ oligomer frequency distribution, photo-induced cross-linking of unmodified proteins (PICUP), to perform "scanning PICUP." Tyr, a reactive group in PICUP, was substituted at position 1, 10, 20, 30, or 40 (for A␤40) or 42 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
86
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(95 citation statements)
references
References 78 publications
(117 reference statements)
8
86
1
Order By: Relevance
“…Gel electrophoresis experiments have shown that A␤ peptides exist as monomers or oligomers of the sizes up to tetramer at micromolar concentration. 12,59 It follows from the electron microscopy studies that the dimers and tetramers have overall spherical shape with the diameter D increasing from 18 Å ͑dimer͒ to 220 Å ͑tetramer͒. 12 The experimental size of the dimer is in a good agreement with our estimate of the size of the dimer core ͑D =2R c =22 Å͒.…”
Section: Comparison Of Experiments and Simulationssupporting
confidence: 68%
See 1 more Smart Citation
“…Gel electrophoresis experiments have shown that A␤ peptides exist as monomers or oligomers of the sizes up to tetramer at micromolar concentration. 12,59 It follows from the electron microscopy studies that the dimers and tetramers have overall spherical shape with the diameter D increasing from 18 Å ͑dimer͒ to 220 Å ͑tetramer͒. 12 The experimental size of the dimer is in a good agreement with our estimate of the size of the dimer core ͑D =2R c =22 Å͒.…”
Section: Comparison Of Experiments and Simulationssupporting
confidence: 68%
“…At the same time, experiments detect a continuous distribution of A␤ species from monomers to tetramers. 12,59 The likely source of this discrepancy is an elevated A␤ concentration used in our study. The experimental measurements are performed at micromolar concentrations, whereas the A␤ concentration in the simulations is in the millimolar range ͑that constitutes a 10 3 difference in concentrations͒.…”
Section: Comparison Of Experiments and Simulationsmentioning
confidence: 71%
“…Most likely an efficient stabilization should lock the molecule in the socalled "␣-basin" (a free energy surface dominated by ␣-helical structures with minima of comparable free energies separated by low barriers (72)), avoiding the migration toward the "␤-basin." Such ␣-helix 3 ␤-sheet conversion going through progressively looser helical segments can be hampered by targeting either the intact ␣-helix with ligand molecules (73) or the structurally independent folding units (turnlike structures) present in the peptide (72,74). The presence of SDS, used as a helix stabilizer, does lengthen the fibrillation time (the lag time of the onset of fibrillation) but does not abolish hCT aggregation.…”
Section: Discussionmentioning
confidence: 99%
“…A turn at Ser 8 -Gly 9 might be particularly important because it can bring the N-terminal quarter of the peptide into contact with the central hydrophobic cluster region. Maji et al (56) proposed that competition between the N and C termini to form a stable complex with the central hydrophobic cluster underlay these effects. For example, a single amino acid substitution, Asp 1 3 Tyr, alters substantially the A␤ assembly kinetics and oligomer size frequency distribution (56).…”
mentioning
confidence: 99%
“…Maji et al (56) proposed that competition between the N and C termini to form a stable complex with the central hydrophobic cluster underlay these effects. For example, a single amino acid substitution, Asp 1 3 Tyr, alters substantially the A␤ assembly kinetics and oligomer size frequency distribution (56). The proximity of His 6 and Asp 7 to the putative Ser 8 -Gly 9 turn suggests that the English and Tottori mutations may affect this structural element, and through this effect, alter overall peptide assembly.…”
mentioning
confidence: 99%